2018
DOI: 10.3390/en11113071
|View full text |Cite
|
Sign up to set email alerts
|

Financing the Renovation of the Cypriot Building Stock: An Assessment of the Energy Saving Potential of Different Policy Scenarios Based on the Invert/EE-Lab Model

Abstract: Despite various government policies promoting energy efficiency in buildings over the last 15 years, Cyprus is still associated with a large untapped energy efficiency potential in this sector. The impact of different policy scenarios on future energy needs of the building sector in Cyprus is explored by first reviewing the current status of the building stock in Cyprus and existing national landscape of energy efficiency policies. Various new policies are then proposed to complement the existing framework and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Bucharest, Prague and Vienna. In [62], the thermal energy needs for Cypriot residential buildings are assessed. For a single-family house constructed after 2006, the annual heating and cooling needs are about 36 kWh/m 2 and 50 kWh/m 2 , respectively.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Bucharest, Prague and Vienna. In [62], the thermal energy needs for Cypriot residential buildings are assessed. For a single-family house constructed after 2006, the annual heating and cooling needs are about 36 kWh/m 2 and 50 kWh/m 2 , respectively.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…He et al [8] demonstrated through empirical research that the SEU financing mechanism can be an effective business model that supports building retrofitting. Economidou et al [23] established a professional financing platform as an effective way to enhance the confidence of other participants. Guo et al [24] analyzed the effectiveness evaluation content of the operation of the building energysaving retrofitting financing platform from the two levels of the operating mechanism and the behavior of the operating subject.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Article [6, [84][85][86][87][88][89][90][91] Conference paper [92][93][94][95][96][97][98][99][100][101][102][103][104][105] [ [106][107][108][109][110][111][112] Review [113][114][115][116][117] After every publication in Table 1 was accurately analyzed, it demonstrates that the methodologies employed are rather heterogeneous, and sometimes they even show conflicting results. Hardly any research proposes a comprehensive study, covering all the aspects that should be considered, from the early audits to the final decision-making processes.…”
Section: Type Of Document Not Open Access Open Accessmentioning
confidence: 99%
“…Then, ref. [88] analyzed the potential of implementing energy efficiency actions on the building stock in Cyprus, and identified policy solutions to enhance this potential.…”
Section: Statistical Approaches In Building Stocksmentioning
confidence: 99%